Inheritance Rights in Cases of Euthanasia: Analyzing Legal and Ethical Complexities - Abubakar, Fatum; Salim, Mohammad Salim (Antmind Review: Journal of Sharia and Legal Ethics, 2024)
This study analyzes the implications of inheritance law related to euthanasia, focusing on legal comparisons in different jurisdictions and perspectives of Islamic law. This study highlights legal loopholes that often arise in cases of euthanasia related to inheritance distribution, especially in the context of the legal system that regulates such actions. Through the approach of analyzing legal literature, sharia maqashid, and jurisdictional comparison, it was found that there was a significant variation in the legal treatment of inheritance claims by individuals involved in euthanasia. In some jurisdictions, such as the Netherlands and Belgium, inheritance claims are still possible with certain conditions, while other jurisdictions, including Indonesia, do not yet have explicit regulations. This study also emphasizes the importance of analyzing aspects of written consent, medical conditions, and moral and ethical principles in deciding inheritance rights. From the perspective of Islamic law, it is found that the principle of preserving the soul (hifz al-nafs) is the basis for rejecting the act of euthanasia. These findings make an important contribution to understanding the relationship between euthanasia and inheritance, as well as offering a legal discourse that supports the development of regulations based on justice, ethics, and human values. This research is a foothold for policymakers to overcome regulatory gaps related to euthanasia in the context of inheritance law.